INTEGRATED COLLABORATIVE RESPONSE MODEL: PANACEA FOR URBAN FIRE DISASTER RESPONSE CHALLENGES IN KANO METROPOLIS, NIGERIA - YUNUS, SULAIMAN (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Globally, fire service departments are faced with tremendous challenges which have significantly increased human and property exposure to fire disasters. This study aimed at identifying and examining the challenges faced by fire service department in Kano metropolis with a view to evolving solutions and proposing a prospective operational model for fire disaster risk reduction and sustainable development. Quantitative and qualitative data were collected in addition to conducting GPS surveying which obtained the locational attributes of fire incidents. Cluster and random sampling were used to select incident clusters from which respondents were derived, and fire stations where key informants were selected respectively. Simple statistics and ratio analysis were conducted for adequacy assessments, while content analysis was conducted to identify major challenges faced. It was found that presently, in Kano metropolis, firefighter-population and fire truck-population ratios are approximately 1:10,830 and 1:393,130 respectively which is approximately 39 times the ratio proposed by UFOA in 2011. It is concluded that the existing centralized response strategy, apparatuses and personnel were found to be obsolete, inadequate and responsible for the inefficiency. Provision of adequate personnel and updated apparatus in addition to embracing integrated collaborative response approach is recommended for efficient response system.